DIVERSITAS, DISTRIBUSI DAN KELIMPAHAN GLASS EEL DI MUARA SUNGAI PALU - Wahyudi, Deddy (JSTT, 2016)
Eel (Anguilla sp.) Including one of the important fish rnelakukan displacement (migration) from the sea to freshwater environments (migration anadromous) for himself and further maturation kernbali to sea (migration katadromous), to perform spawning. The second migration is the whole life cycle of eels. Almost all of the estuary in Indonesia which can deep sea found Elver eels. This study aims to determine the diversity, distribution, abundance and size structure of glass eel in Palu River estuary. This research was conducted for six months ie in September 2014 to February 2015. The sampling locations estuary of Palu River. Sampling was done every month dark during the study, further samples are identified by Anodorsal vertebrae (ADV) and Caudal spot (CS) or Tail Spot (TS). The results showed that the diversity index of glass eel are migratory in the mouth of Palu River has a level of diversity of small and stability of the community is low, for an index of uniformity showed that the distribution of individuals among species uneven or there are certain types of dominant while the dominance index showed that there is one species dominate while doing migration of Palu River that is Anguilla marmorata. The distribution of glass eel on a monthly basis show a uniform pattern of spread. Eel abundance of glass eels are affected by the tides that occur in the mouth of Palu River. Glass eels are doing ruaya anadromous (migrating) to the mouth of Palu River month period September 2014 to February 2015 consists of three species, namely Anguilla marmorata, Anguilla sp. and Anguilla bicolor pacifica.